Indigenous Language Knowledge and Educational Attainment Among First Nations People: Trends Over Time - Bougie, Evelyne; Kohen, Dafna; Guèvremont, Anne (International Indigenous Policy Journal, 2018)
This study investigated whether associations between Indigenous language knowledge and educational outcomes might be changing for cohorts of language speakers over time. Using Census and National Household Survey data, educational attainment for First Nations people aged 20 to 34 was examined at four time points (1996, 2001, 2006, and 2011), separately for those able versus unable to speak an Indigenous language and separately for those living on and off reserve. Findings point to improvements in levels of education for Indigenous language speakers among First Nations people living on and off reserve. Findings should be interpreted with caution as differences in educational attainment may reflect differences between language speakers and non-speakers that go beyond the ability to speak an Indigenous language.